#### Answer

$2^{-3}x^{-15}y^{9}$

#### Work Step by Step

$(2x^5y^{-3})^{-3}=(2)^{-3}(x^5)^{-3}(y^{-3})^{-3}=2^{-3}x^{5(-3)}y^{(-3)(-3)}=2^{-3}x^{-15}y^{9}$

Published by
McDougal Littell

ISBN 10:
0618595414

ISBN 13:
978-0-61859-541-9

$2^{-3}x^{-15}y^{9}$

$(2x^5y^{-3})^{-3}=(2)^{-3}(x^5)^{-3}(y^{-3})^{-3}=2^{-3}x^{5(-3)}y^{(-3)(-3)}=2^{-3}x^{-15}y^{9}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.